Phytochemical study of oleoresin extracted from Copaifera reticulata Ducke (Leguminosae-Caesalpinioidade) in a sustainable management area (Research, Society and Development, 2021)
Among the plant species that produce oils, the genus Copaifera L stands out. It consists of species of high economic and ecological value, its trees exude an oleoresin popularly known as copaiba oil, whose medicinal, cosmetic and industrial properties are widely described in the literature. In this sense, the main objective of this study was to analyze the phytochemical elements present in the oleoresin of the Copaifera reticulata Ducke species, identifying the phytochemical components that are repeated in each copaibeira and then to analyze, through Pearson's correlation matrix, the significance relationship of the chemical elements of the soil with the DAP of the selected trees. The study was conducted in the managed forest located at the São Roque Agroecological Farm in the municipality of Mojú-PA. This research is a quantitative analysis and the results showed that in relation to K, P and Na, the highest concentrations of these elements were observed in the soil of trees 1 (5.0 mg/dm3), tree 10 (17.5 mg/dm3) and tree 7 (8, 5 mg/dm3) respectively. Ca and Ca+ Mg contents were high in the areas of the first, second and third individuals of the species C. reticulata, with values for Ca: 0.9; 1,2; 2.4 and for Ca+Mg: 1.4; 1.7; 3.2, respectively. The content of H + Al (potential acidity) was high in the soils of individuals 4 (1.4 cmolc/dm3), 5 (1.5 cmolc/dm3) and 7 (1.5 cmolc/dm3). And through the analysis of Pearson's correlation, when comparing the diameters and the pH of the water, there is a positive correlation (r = 0.622), that is, the larger the diameter of the trees, the greater the percentage of pH of the Water. Another positive correlation occurred between the percentages of Ca and Ca+Mg (r = 0.993), that is, the higher the percentage of Ca in the soil, the higher the percentage of Ca + Mg. Regarding phytochemical characterization, only 3 trees produced oil-resin with an identification percentage of 96.1%, 86.6% and 70.7% corresponding to the inventory trees with numbers 96, 106 and 153 (trees 6, 7 and 10) there was a difference in the concentration rate and in the phytochemical composition of the analyzed oils. The elements (E)-caryophyllene, (E)-alpha-bergamothene and beta-bisabolene were constant in the analyzed oils and considered the most important in terms of their biological activities. The averages of Beta-elemene phytochemicals content; (E)-caryophyllene; (E)-alpha-bergamothene; (E)-beta-farnesene; (Z)-alpha-bisabolene; β-bisabolene; Beta-sesquiphelandrene and Caurene of the three trees were compared with the averages of Content of the same phytochemicals from three bibliographic studies used as references and it was found that there are no significant differences in the averages of content of phytochemicals adopted as a significance level of 5% (p < 0.05). The results obtained in the present work reinforce even more the importance of the copaiba oleoresin from the Amazon region, contributing to the expansion of the chemical knowledge of the species Copaifera reticulata Ducke.